PENGARUH WAKTU FIKSASI FORMALIN TERHADAP JUMLAH NEURON NITRERGIK PADA PLEKSUS MIENTERIKUS USUS HALUS MARMOT LOKAL - , NARIS RAHMAWATI; , Dr.drh. Amelia Hana, M.P. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research was conducted to purpose the number of neuron nitrergic local guinea pig intestine with formalin fixation on different time. Animals used were five male local guinea pig, weight 409-615 gram and healthy. Local guinea pig adapted for six days, then anaesthetized with chloroform, then euthanation. The segment of small intestine is the duodenum, jejunum, and ileum were taken. Each segment divided into three pieces to be treated times different fixation in formalin 10% (30 minutes, 45 minutes and 60 minutes). The staining techniques used NADPH-diaphorase. Data on the number of neuron/cm² were statistically analyzed with anova one way. The research showed the number of neuron nitrergic plexus myentericus duodenum in the treatment formalin 10% for 30 minutes, 45 minutes, and 60 minutes were 3133.27+184.38 neuron/cm², 3150.12+294.17 neuron/cm², and 3342.64+744.43 neuron/cm² respectively. The number of neuron nitrergic plexus myentericus jejunum in the treatment formalin 10% for 30 minutes, 45 minutes, and 60 minutes were 3754.15+698.10 neuron/cm², 3537.56+514.17 neuron/cm², and 3638.64+344.73 neuron/cm² respectively. The number of neuron nitrergic plexus myentericus jejunum in the treatment formalin 10% for 30 minutes, 45 minutes, and 60 minutes were 4079.03+375.04 neuron/cm², 3963.51+345.98 neuron/cm², and 3467.77+421.94 neuron/cm² respectively. It was concluded that fixation formalin 10% with 30 minutes, 45 minutes and 60 minutes had no effect on either the number of neuron nitrergic in the duodenum, jejunum, and ileum.